2015
DOI: 10.1186/s13068-015-0379-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of lignin inhibition of enzymatic biomass deconstruction

Abstract: BackgroundThe conversion of plant biomass to ethanol via enzymatic cellulose hydrolysis offers a potentially sustainable route to biofuel production. However, the inhibition of enzymatic activity in pretreated biomass by lignin severely limits the efficiency of this process.ResultsBy performing atomic-detail molecular dynamics simulation of a biomass model containing cellulose, lignin, and cellulases (TrCel7A), we elucidate detailed lignin inhibition mechanisms. We find that lignin binds preferentially both to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(143 citation statements)
references
References 103 publications
2
133
0
Order By: Relevance
“…There have been several studies conducted in recent years on the non‐specific binding of cellulases to lignin (Pfeiffer et al, ; Vermaas et al, ; Yarbrough et al, ). Though most T. reesei cellulases contain a family 1 Carbohydrate‐Binding Module (CBM1), which is a key determinant driving full‐length cellulase binding to lignin (Vermaas et al, ), other enzyme properties that are unique to each cellulase family can result in differential binding affinity toward lignin (Palonen et al, ). For example, β‐glucosidases (which lack a CBM1) have also been shown to bind to lignin in complex mixtures (Yarbrough et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies conducted in recent years on the non‐specific binding of cellulases to lignin (Pfeiffer et al, ; Vermaas et al, ; Yarbrough et al, ). Though most T. reesei cellulases contain a family 1 Carbohydrate‐Binding Module (CBM1), which is a key determinant driving full‐length cellulase binding to lignin (Vermaas et al, ), other enzyme properties that are unique to each cellulase family can result in differential binding affinity toward lignin (Palonen et al, ). For example, β‐glucosidases (which lack a CBM1) have also been shown to bind to lignin in complex mixtures (Yarbrough et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that enzyme binding to noncellulose molecules, such as lignin, can take place during enzymatic hydrolysis and that this leads to decreased hydrolysis efficiency . In the present study, enzyme activity on corn stover was visualized.…”
Section: Resultsmentioning
confidence: 82%
“…Two hypotheses can be postulated to explain the positive effect of the enzyme addition: (i) additional hydrolytic enzymes can attach to humic acids, preventing their scavenging behaviour against intrinsic hydrolytic enzyme production by abundant hydrolytic bacteria within anaerobic sludge (Fernandes et al 2015); (ii) competition between HA and enzymes to bind the cellulose particles. Lignin has similar functional groups as HA, and Vermaas et al (2015) found that lignin preferentially binds to the hydrophobic side of the cellulose and also to the specific residues on the cellulose-binding modules of the enzymes that are critical for cellulose binding to cellulases. Our results can support both hypotheses by showing that the intrinsic enzyme production from hydrolytic bacteria can maintain the hydrolytic activity when binding sites of HA were inactivated by enzyme addition or preventing HA to bind cellulose particles.…”
Section: Discussionmentioning
confidence: 99%